Kompetensi Profesional Guru dalam Pengelolaan Pembelajaran Matematika Kelas Rendah di MI NW Keruak - Laili, Husnul (TSAQOFAH, 2022)
Professional competence is the ability to master learning material widely and in depth, and adjusted to expertise in the field mastered as well as in their respective duties and responsibilities. Mastery of teaching materials is included with interesting learning methods, responsibility for their duties, and harmony among fellow teachers. Learning management is a process of interaction between students and teachers in the learning environment. This study aims to determine the importance of teacher professional competence in learning management, teacher professional strategies and learning evaluation at MI NW Keruak. This research uses qualitative research. Data collection techniques were carried out through interviews, observation and documentation studies. The research subjects were school principals, teachers and students of MI NW Keruak. The results of the study show: (1) the competence of teachers in planning lessons in preparing lesson plans, compiling syllabus, planning media and learning resources and planning learning evaluations in accordance with established instructions, but there are some teaching teachers who do not make lesson plans; (2) the teacher's professional strategy in implementing learning, namely: mastering the material, structure, concept and mindset science that supports the subjects being taught. This is done by reviewing the material before continuing, adjusting the material to the media/learning resources; and (3) the evaluation of the learning provided by the teacher is in accordance with the learning objectives that have been set, which includes the value of student character, assessment of the ability to understand concepts, the value of student skills and the value of attitudes in the learning process. Evaluation is carried out at the end of one semester.